Recovery of Phosphate and Ammonium from Dairy Cow Urine by Struvite Crystallization with Vertical Reactor - Luluk Edahwati; Sutiyono; Rizqi Rendri Anggriawan (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Excess phosphate (PO43-) and ammonium (NH4+) in wastewater can cause environmental damages, such as pollutants and eutrophication in water. Dairy cow urine is a dangerous liquid waste that contains high amounts of phosphate and ammonium. The removal of PO4 and NH4 components can be done by crystallizing them into struvite fertilizers. Struvite (MgNH4PO4.6H2O) is a mineral formed from magnesium, ammonium, and phosphate with the equimolar ratio. The crystallization process of struvite is carried out using a vertical reactor. MAP solution (magnesium ammonium phosphate) is prepared by reacting MgCl2, H3PO4, and dairy cow urine with MAP molar ratio of 1 : 1 : 1 and KOH 1N. The study run in pH 8; 8.5; 9; 9.5; 10 and temperature variations of 25, 30, 35, 40, 45˚C in vertical reactor continuously. The struvite precipitate was filtered and dried, it is analyzed by XRF to determine the struvite composition and SEM to determine the morphology of the struvite. The results showed that the best percentage of phosphate and ammonium was at 45˚C and pH 9.5, it was 33.2% and 27.9%.